Peningkatan Pengetahuan Ibu Hamil Terhadap Pemberian ASI Ekslusif di Kelas Ibu Hamil - Sehmawati; Anggita Septyani Permatasari; Rosmala Kurnia Dewi (Universitas Ngudi Waluyo, 2022)
Breastfeeding is one of the best investments for survival and improving the health, social and economic development of individuals and the nation. The high infant mortality rate can be handled early on by giving breast milk (ASI). Recommendations for exclusive breastfeeding for up to 6 months are still too difficult to implement. So it is necessary to increase the coverage of exclusive breastfeeding for babies Increased Knowledge of Pregnant Women on Exclusive Breastfeeding in Classes for Pregnant Women Community service will be held on Tuesday, June 28, 2022, at 09.00 at PMB Sunarti, Ngraji Village, along with class activities for pregnant women. The first stage was the introduction between the team and participants consisting of pregnant women, followed by distributing questionnaires about exclusive breastfeeding. The second stage is the working phase, which is providing health education about breastfeeding and exclusive breastfeeding preparation. Health education is provided by means of lectures, discussions, questions and answers, and distributing leaflets about exclusive breastfeeding. The third stage is the evaluation stage, namely by asking participants whether they have understood the extension material, by asking questions and participants answering questions. In addition to asking direct questions, the servant also gave the same questionnaire. This outreach activity succeeded in increasing the knowledge of participants, which was marked by an increase in knowledge scores, from an average score of 72 to an average score of 85. Community service in the pregnant women class at TPMB Sunarti is very appropriate and efficient from the beginning of pregnancy so that pregnant women are able to prepare properly for exclusive breastfeeding. AbstrakMenyusui salah satu investasi terbaik untuk kelangsungan hidup dan meningkatkan kesehatan, perkembangan sosial serta ekonomi individu dan bangsa Tingginya angka kematian bayi dapat ditangani sejak awal dengan cara pemberian Air Susu Ibu (ASI). Rekomendasi pemberian ASI ekslusif sampai 6 bulan masih terlalu sulit untuk dilaksanakan. Maka perlu upaya meningkatkan cakupan ASI ekslusif pada bayi. Peningkatan Pengetahuan Ibu Hamil Terhadap Pemberian ASI Ekslusif Di Kelas Ibu Hamil Pengabdian ini dilaksanakan pada hari Selasa tanggal 28 Juni 2022 pada pukul 09.00 bertempat di PMB Sunarti Desa Ngraji bersamaan dengan kegiatan kelas ibu hamil. Tahap pertama perkenalan antara tim dengan peserta yang terdiri dari ibu hamil, dilanjutkan dengan penyebaran kuesioner tentang ASI eksklusif. Tahap kedua adalah fase kerja yaitu memberikan pendidikan kesehatan tentang ASI dan Persiapan Menyusui Eksklusif. Pendidikan kesehatan diberikan dengan metode ceramah, diskusi, tanya jawab, dan penyebaran leaflet tentang ASI eksklusif. Tahap ketiga adalah tahap evaluasi yaitu dengan menanyakan kepada peserta apakah sudah memahami materi penyuluhan, dengan cara memberi pertanyaan dan peserta menjawab pertanyaan. Selain memberikan pertanyaan secara langsung, pengabdi juga memberikan kuesioner yang sama.Kegiatan penyuluhan ini berhasil meningkatkan pengetahuan peserta yang ditandai dengan peningkatan skor pengetahuan, dari skor rata-rata 72 menjadi skor rata-rata 85. Pengabdian masyarakat pada kelas Ibu hamil di TPMB Sunarti sangat tepat dan efisiensi diberikan sejak awal masa kehamilan agar ibu hamil mampu mempersiapkan dengan baik pemberian ASI Ekslusif.